2010
DOI: 10.1016/j.eatbeh.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness mediates the relation between disordered eating-related cognitions and psychological distress

Abstract: The present study investigated whether mindfulness mediates the relation between disordered eating-related cognitions and negative psychological outcomes within a nonclinical college sample. Disordered eating-related cognitions were positively associated with general psychological ill-health and emotional distress in interpersonal contexts and inversely related to mindfulness. Mindfulness, which was also inversely related to general psychological ill-health and emotional distress, was found to partially mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 21 publications
6
20
0
1
Order By: Relevance
“…Furthermore, Carson and Langer (2006) suggest that mindfulness contributes to selfesteem through promoting authenticity instead of social comparison and acceptance of the self instead of evaluation. In support of this premise, preliminary results indicate that dispositional mindfulness is inversely related to disordered eating-related cognitions (Lavender et al, 2009) and potentially mediates the link between disordered eating-related cognitions and psychological distress (Masuda and Wendell, 2010). Furthermore, women high in dispositional mindfulness are reportedly more satisfied with their body and are less likely to engage in social comparison processes typically indicative of body-related shame (Dijkstra and Barelds, 2011).…”
Section: Mindfulnesssupporting
confidence: 49%
“…Furthermore, Carson and Langer (2006) suggest that mindfulness contributes to selfesteem through promoting authenticity instead of social comparison and acceptance of the self instead of evaluation. In support of this premise, preliminary results indicate that dispositional mindfulness is inversely related to disordered eating-related cognitions (Lavender et al, 2009) and potentially mediates the link between disordered eating-related cognitions and psychological distress (Masuda and Wendell, 2010). Furthermore, women high in dispositional mindfulness are reportedly more satisfied with their body and are less likely to engage in social comparison processes typically indicative of body-related shame (Dijkstra and Barelds, 2011).…”
Section: Mindfulnesssupporting
confidence: 49%
“…The purpose of the study and instructions for completing shown an adequate Chronbach's alpha of .88. 26 In the present study, Chronbach's alpha of this measure was .87.…”
Section: Procedures and Measuresmentioning
confidence: 84%
“…Furthermore, trait mindfulness has been associated with lower levels of bulimic symptoms and disordered eating-related cognitions in college populations (Adams, McVay et al, 2012; Lavender et al, 2009; Masuda & Wendell, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…In sum, mindfulness may be beneficial for improving attitudes about body weight and shape (Adams, McVay et al, 2012; Delinsky & Wilson, 2006; Lavender et al 2009; Masuda & Wendell, 2010) and promoting smoking cessation (Brewer et al, 2011; Davis et al, 2007). Furthermore, mindfulness is best viewed as a multidimensional construct (Baer et al, 2006; Lavender et al, 2011).…”
Section: Introductionmentioning
confidence: 99%